MORPHO-PHYSIOLOGICAL BEHAVIOR OF Commelina benghalensis IN RESPONSE TO HERBICIDES APLIED IN POST-EMERGENCY - Krolikowski, Valquiria; Carvalho, Fernando Tadeu de [UNESP]; Teodoro, Paulo Eduardo (Univ Federal Uberlandia, 2017)
Given the difficulty in controlling dayflower, the aim was to identify what herbicide provides the better control of Commelina benghalensis and the better developmental stage for its application. The plants were grown in pots containing 2 L Bioplant substrate and soil being maintained throughout the trial at a greenhouse. Experimental design was completely randomized with four replications in factorial 8 x 5, so seven herbicides in recommended commercial rates (atrazine, carfentrazone, flumioxazin, glyphosate, MSMA, nicosulfuron and paraquat) and control applied at 5 phenological stages adjusted to BBCH scale. It was observed that the plant phenological stage affects the efficiency of chemical control. Plants at early development stages (BBCH 11 and 12) were more susceptible to herbicides, occurring control in its entirety only with atrazine, carfentrazone, MSMA and paraquat. Despite suffering injuries, C. benghalensis showed tolerance to others treatments.
Keywords: Dayflower; Phenological stage; Tolerance